1994
DOI: 10.1099/00222615-40-3-214
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance to antiseptics and disinfectants in coagulase-negative staphylococci

Abstract: Summary. The occurrence of resistance to antiseptics and disinfectants in clinical isolates of coagulase-negative staphylococci (CNS) was examined. Of 164 clinical strains of CNS isolated in the early 1980s, 65 were resistant to cationic antimicrobial compounds such as cetyltrimethylammonium bromide. Further characterisation of 40 resistant isolates by DNA-DNA hybridisation analysis and phenotypic resistance studies revealed that this resistance was mediated by the multidrug export genes qacA and qacC, charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 26 publications
(6 reference statements)
5
104
0
1
Order By: Relevance
“…An existing cross-resistance between QACs and aminoglycosides, codified by plasmids, has been reported in MRSA strains, leading to the suggestion that the extensive use of cationic agents in the hospital environment can be a factor responsible for the emergence of resistant strains to antibiotic agents (6,25). Recently, resistance to cationic agents and to antibiotics mediated by the same plasmids has been also observed in coagulase-negative staphylococci (CoNS), microorganisms associated with infections in implanted foreign bodies (12). Tennent and coleagues (24) suggested that staphylococci evade destruction because the protein specified by the qacA determinant, located in a plasmid locus, is a cytoplasmic membrane-associated protein involved in an efflux system that actively reduces intracellular accumulation of the QAC.…”
Section: Discussionmentioning
confidence: 99%
“…An existing cross-resistance between QACs and aminoglycosides, codified by plasmids, has been reported in MRSA strains, leading to the suggestion that the extensive use of cationic agents in the hospital environment can be a factor responsible for the emergence of resistant strains to antibiotic agents (6,25). Recently, resistance to cationic agents and to antibiotics mediated by the same plasmids has been also observed in coagulase-negative staphylococci (CoNS), microorganisms associated with infections in implanted foreign bodies (12). Tennent and coleagues (24) suggested that staphylococci evade destruction because the protein specified by the qacA determinant, located in a plasmid locus, is a cytoplasmic membrane-associated protein involved in an efflux system that actively reduces intracellular accumulation of the QAC.…”
Section: Discussionmentioning
confidence: 99%
“…The Qac multipledrug-resistant pumps QacA, QacB, and QacC have been shown to confer resistance to various antimicrobial organic cations. The QacA pump is responsible for high-level resistance to both biguanidines (e.g., chlorhexidine) and diamidine (e.g., pentamidine) (13), and the QacC (Smr) pump is responsible for quaternary ammonium resistance (7). The difference between QacB and QacA is a single amino acid substitution at position 323, leading to a lower resistance level of biguanidines and diamidine in QacB (13).…”
Section: Resultsmentioning
confidence: 99%
“…However, detection of resistance to propamidine isethionate in 11.2% of the isolates was significant. Propamidine isethionate and quaternary ammonium compounds are components of household disinfectants and antiseptics [36,371, and resistance to propamidine isethionate is usually linked to resistance to quaternary ammonium compounds [36,37]. Therefore their resistance may diminish the usefulness of antiseptics containing them as hand-washing agents for removing enterotoxigenic staphylococci from the hands and preventing their cross-contamination.…”
Section: Discussionmentioning
confidence: 99%